Right ventricular ejection fraction during exercise as a predictor of mortality in patients awaiting lung transplantation: a cohort study. Issue 4 (8th April 2013) - Selimovic, Nedim; Andersson, Bert; Bech-Hanssen, Odd; Lomsky, Milan; Riise, Gerdt C; Rundqvist, Bengt
Abstract : Objective: The occurrence of right ventricular dysfunction is a well-known indicator of poor prognosis in patients with chronic cardiopulmonary disease. The role of right ventricular ejection fraction (RVEF) at rest and during exercise as predictors of outcome in patients awaiting lung transplantation (LTx) is unclear. Design: We performed a retrospective analysis of lung transplant candidates who had undergone equilibrium radionuclide angiography (ERNA), to determine baseline and exercise RVEF. Lung function, gas exchange and pulmonary haemodynamics were also assessed. Patients and main outcome measures: 152 patients (mean age 47±11 years; 59% women) were included in the study. Primary endpoint was death on the waiting list for LTx. Main diagnoses were α-1 antitrypsin deficiency (n=35), chronic obstructive pulmonary disease (n=41), cystic fibrosis (n=10), interstitial lung disease (n=34) and pulmonary arterial hypertension (n=32). Twenty-five patients died (16, 4%). LTx was performed in 121 patients. The mean RVEF at rest was equal to mean RVEF during exercise (38±12%). In univariate analysis RVEF at rest, RVEF during exercise, heart rate and forced volume capacity (FVC) % of predicted were factors significantly associated with risk of death. In multivariate analysis RVEF during exercise and FVC% of predicted were independent predictors of death. Conclusions: In lung transplant candidates, right ventricular function during exercise is a stronger predictor of outcome than right ventricular function at rest. RVEF during exercise assessed by ERNA could be incorporated into priority-based allocation algorithms for LTx.